Rocky V (1990) [videorecording (DVD)] - Avildsen, John G., 1935-2017; Stallone, Sylvester; Shire, Talia; Meredith, Burgess, 1907-1997 (MGM DVD, 2006)
Rocky and his family must move to their old, low-rent neighborhood after all their money is lost by an an unscrupulous financial advisor and injuries force his retirement from the ring. As Rocky tries to resolve the resentment held by his son, a young boxer Rocky trained publicly taunts his mentor, and Rocky realizes he must fight once more.